Knowledge, attitude, and practices about male infertility among men and women in slums of Chennai, Tamil Nadu: a cross-sectional study - Chinnaiyan, Saravanan; Babu, Bhavya (International Journal Of Community Medicine And Public Health, 2020)
Background: Infertility is a major public health problem that affects 15% of the global population. Fertility is the ability to conceive pregnancy and has a positive social value whereas; infertility has a negative social value in Indian culture. So, infertility is a serious problem in developing and undeveloped countries are more than of biological. Aim: To assess the knowledge, attitude, perception, and practices, and myths about male infertility in the slums of Chennai. Methods: This is a cross-sectional study carried out in the Slums of Chennai from January 2020 to March 2020. A total of 125 male and 125 female participants of the age group ≥18 years were recruited for the study by simple random sampling. Results: The study revealed that there is adequate knowledge of the common causes of infertility, but clinical knowledge is comparatively low. Both men and women shared almost equal knowledge of infertility. Conclusion: Educational programmes, regular campaigns by Accredited social health activists (ASHAs) and the involvement of community are recommended to increase knowledge about the causes of infertility as well as decrease the stigma associated with this condition.